2007
DOI: 10.1007/s10886-007-9275-4
|View full text |Cite
|
Sign up to set email alerts
|

Using Generic Pheromone Lures to Expedite Identification of Aggregation Pheromones for the Cerambycid Beetles Xylotrechus nauticus, Phymatodes lecontei, and Neoclytus modestus modestus

Abstract: Males of several species of longhorned beetles in the subfamily Cerambycinae produce sex or aggregation pheromones consisting of 2,3-hexanediols and/or hydroxyhexanones. We tested the hypothesis that this diol/hydroxyketone pheromone motif is highly conserved within the subfamily, and the resulting prediction that multiple cerambycine species will be attracted to compounds of this type. We also tested the concept that live traps baited with generic blends of these compounds could be used as a source of live in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
95
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(106 citation statements)
references
References 24 publications
11
95
0
Order By: Relevance
“…Our data support the predictions of Hanks et al (2007) that multiple species in the subfamily Cerambycinae would be attracted to compounds in the 2,3-diol/hydroxyketone motif. We found that racemic hydroxyketones (i.e., K6, k8) increased the efficacy of detecting three of eight species of Cerambycinae: A. colobotheoides, P. testaceus, and M. minor.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our data support the predictions of Hanks et al (2007) that multiple species in the subfamily Cerambycinae would be attracted to compounds in the 2,3-diol/hydroxyketone motif. We found that racemic hydroxyketones (i.e., K6, k8) increased the efficacy of detecting three of eight species of Cerambycinae: A. colobotheoides, P. testaceus, and M. minor.…”
Section: Discussionsupporting
confidence: 88%
“…In contrast to the Lepidoptera, in which attraction of a particular moth species to a synthetic lure is highly dependent on the relative ratio and chirality of pheromone components (Roelofs & CardĂ©, 1977), longhorn beetle pheromones often attract several species in the same genus or subfamily and thus have good potential as survey tools of native and exotic Cerambycids (Millar et al, 2009;. Hanks et al (2007) found that individual species of Cerambycinae usually emitted specific enantiomers, e.g., (R)-3-hydroxyhexan-2-one, but the presence of other enantiomers in synthetic lures did not reduce attraction; they hypothesized that the 2,3-diol/hydroxyketone pheromone motif was highly conserved within the subfamily and predicted that multiple Cerambycinae species would be attracted to compounds of this type. Similarly, (E)-6,10-dimethyl-5,9-undecadien-2-ol (fuscumol), the aggregation pheromone of Tetropium fuscum (Fabr.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is considerable circumstantial evidence that female-produced sex attractant pheromones are widespread within the Prioninae (e.g., Rotrou 1936;Edwards 1961;Benham and Farrar 1976;Gwynne and Hostetler 1978), so we anticipate that pheromones of other species, particularly congeners of P. californicus, will soon be reported, now that the basic methods and a "lead" compound have been characterized. It should also be noted that the pheromone of P. californicus is entirely different in structure from the male-produced pheromones of species in other subfamilies of the Cerambycidae (e.g., Hanks et al 2007;Ray et al 2009), and femaleproduced pheromones of two species that are apparently closely related to the Cerambycidae: Migdolus fryanus Westwood and Vesperus xatarti Dufour (Leal et al 1994;Boyer et al 1997; taxonomy according to Napp 1994;Bense 1995;Dong and Yang 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggests that there is considerable parsimony among cerambycid species with regard to pheromone biosynthesis and use, with closely related species often sharing pheromone components, or even producing pheromones of apparently identical composition (e.g., Hanks et al, 2007;Mitchell et al, 2011Mitchell et al, , 2013Ray et al, 2012Ray et al, , 2015Hanks and Millar, 2013). For example, ∌60 species within the subfamily Cerambycinae have been shown to emit and are attracted to pheromone compounds with 6, 8, or 10 carbon chains, with carbonyl or hydroxyl groups on carbons 2 and/or 3 (listed in Table S1 of Hanks and Millar, 2016).…”
Section: Introductionmentioning
confidence: 99%